Fair and efficent taxation under partial control - Erwin Ooghe; Andreas Peichl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
We study fair and efficient tax-benefit schemes based on income and non-income factors under partial control. Partial control means that each factor is a specific mixture of unobserved ability (randomly drawn by nature) and effort (chosen by individuals who differ in tastes). Factors differ in the degree of control, ranging from no control (if only ability matters) to full control (if only effort matters). Fairness requires to compensate individuals for differences in well-being caused by differences in abilities, while at the same time preserving well-being differences caused by taste differences. We discuss first the general properties of fair and efficient tax-benefit schemes. Next, we study two special cases income taxation and tagging in detail. Finally, we derive testable conditions for the general case and discuss the empirical implementation.
urn:nbn:de:bsz:180-madoc-354576
Keywords: D6; H2; I3; 330; fairness; redistribution; taxation; tagging; equality of opportunity